High-heat-resistance and high-liquid-absorption ceramic diaphragm as well as preparation method and application thereof

By introducing hydroxyl-containing polymers and boron-containing crosslinking agents into the ceramic diaphragm coating to form a three-dimensional network structure, the problem of insufficient mechanical strength and temperature resistance of the ceramic diaphragm at high temperatures is solved, and a high heat-resistant and high liquid-absorbing ceramic diaphragm is achieved, which improves the cycling performance of the battery cell.

CN119890612AActive Publication Date: 2025-04-25CANGZHOU MINGZHU SEPARATOR TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411878461.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25
Estimated Expiration
2044-12-19

Smart Images

  • Figure BDA0005197548420000091
    Figure BDA0005197548420000091
Patent Text Reader

Abstract

The invention relates to the field of battery diaphragms, in particular to a high-heat-resistance and high-liquid-absorption ceramic diaphragm and a preparation method and application thereof.According to the high-heat-resistance and high-liquid-absorption ceramic diaphragm and the preparation method and application thereof, hydroxyl-containing macromolecules are introduced into a coating, and the hydroxyl-containing macromolecules have good affinity to electrolyte, so that the ceramic diaphragm has good liquid absorption performance; in addition, a boron-containing cross-linking agent is introduced into the coating, and borate ions in an inorganic boric acid aqueous solution can be used as a cross-linking agent to form hydrogen bonds with hydroxyl-containing macromolecules, so that a cross-linking reaction is carried out, and the cycle performance of the battery cell is effectively improved; and 4-vinylphenylboronic acid and ethylene glycol divinyl ether in the organic boric acid solution are copolymerized at high temperature to form a six-membered ring, so that a three-dimensional network structure can be formed in the system within a wider temperature range, the skeleton strength of the ceramic diaphragm coating is improved, and the temperature resistance of the ceramic diaphragm is also improved while the high liquid absorbency is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery diaphragms, and in particular to a highly heat-resistant and highly liquid-absorbent ceramic diaphragm and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have become a hot topic in power technology research in recent years due to their advantages of high specific energy, long cycle life, no memory effect (compared to nickel-chromium batteries), and safety, reliability, and ability to withstand rapid re-discharge. Lithium-ion batteries play an irreplaceable role in widely used electronic devices such as mobile phones, laptops, etc., as well as the emerging electric and hybrid electric vehicles.

[0003] The main structure of lithium-ion batteries includes positive / negative electrode materials, electrolytes, battery separators and battery shell outer packaging materials. Battery separators are an important component of lithium-ion batteries. They play a role in directly separating positive and negative electrodes and preventing battery short circuits. The performance of battery separators directly determines the interface performance, cycle performance and safety performance of batteries. Therefore, excellent separators play a vital role in improving the overall performance of batteries.

[0004] Ceramics are widely used in the coating of diaphragms because they can be dispersed in water and are environmentally friendly, so as to prepare high-temperature resistant ceramic coating diaphragms with good thermal stability. The wettability of electrolyte is an important indicator for evaluating diaphragms. Excellent electrolyte wettability is beneficial to improving the ionic conductivity of the battery. In order to further improve the ability of lithium battery diaphragms to absorb electrolytes, a polymer adhesive containing polar hydrophilic groups is usually introduced into the diaphragm coating. For example, the patent technical document CN108305972B discloses a ceramic coating diaphragm and a preparation method and application thereof. The ceramic coating diaphragm includes a base film and a ceramic coating, wherein the ceramic coating is coated with inorganic particles with polyethylene glycol grafted on the surface, and the inorganic particles are grafted with polyethylene glycol having a hydroxyl group. Although the ceramic coating diaphragm has a fast liquid absorption rate and a high liquid absorption rate, it exhibits a large thermal shrinkage under high temperature conditions, resulting in poor mechanical strength and temperature resistance of the ceramic coating diaphragm at high temperatures.

[0005] In order to solve the above problems, a cross-linkable polymer adhesive can be introduced into the diaphragm coating to form a three-dimensional network structure on the diaphragm surface to increase the mechanical strength and temperature resistance of the ceramic coating diaphragm. For example, patent document CN113964450A discloses a battery diaphragm coating liquid and a preparation method thereof, a battery diaphragm and a battery. In the battery diaphragm coating liquid, due to the interaction force or hydrogen bond between ceramics, adhesives, nanowires and coupling agents, a structure of ... ceramic-coupling agent-nanowire-ceramic-coupling agent-nanowire... is formed, so that the final battery diaphragm has good heat resistance. However, since hydrogen bonds are unstable and may be destroyed when a certain temperature is reached, this method is relatively limited in improving the mechanical strength of the diaphragm at high temperatures.

[0006] Therefore, in view of the above-mentioned related technologies, it is urgent to develop a high heat-resistant, high liquid absorption ceramic diaphragm and its preparation method and application. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a high heat-resistant, high liquid absorption ceramic diaphragm and a preparation method and application thereof, so as to solve the problem of poor liquid absorption performance of ceramic diaphragms in the prior art.

[0008] Based on the above objectives, the present invention provides a high heat-resistant, high liquid-absorbent ceramic diaphragm and a preparation method and application thereof.

[0009] A highly heat-resistant and highly liquid-absorbent ceramic diaphragm, comprising a coating and a substrate, wherein the coating is prepared from the following raw materials in parts by weight: 80-120 parts of ceramic particles, 4-8 parts of hydroxyl-containing polymers, 3-5 parts of a binder, 30-50 parts of a boron-containing crosslinking agent, 0.1-0.5 parts of an auxiliary agent, and 1-2 parts of a dispersant;

[0010] The substrate is composed of any one of polyethylene, polypropylene and polymethylpentene;

[0011] The preparation method of the boron-containing cross-linking agent is as follows:

[0012] S1. dissolving the boron-containing inorganic compound in water, and then adding an inorganic alkaline compound to obtain an inorganic boric acid aqueous solution;

[0013] S2. 4-vinylbenzeneboronic acid, ethylene glycol divinyl ether, 3-chloro-2-hydroxypropyltrimethylammonium chloride, azobisisobutyronitrile, tetrahydrofuran and water are mixed evenly, and reacted at 75-85° C. for 22-24 hours to obtain an organic boronic acid solution;

[0014] S3. Evenly mix the inorganic boric acid aqueous solution and the organic boric acid solution to obtain a boron-containing crosslinking agent.

[0015] Preferably, the hydroxyl-containing polymer is one or more of nano bamboo charcoal powder, nano cellulose, polyvinyl alcohol, polyethylene glycol, and the binder is one or more of styrene-butadiene rubber, polymethyl acrylate, polybutyl acrylate, polyvinyl alcohol, polyvinylidene fluoride, etc.

[0016] Preferably, the auxiliary agent is one or more of succinic acid, fluoroalkyl methoxy ether alcohol, sodium polyacrylate, acetylene glycol vinyl ether, fatty acid polyoxyethylene ether, and polyether modified siloxane, and the dispersant is one or more of sodium polyacrylate, ammonium polyacrylate, carboxylates, and sulfonates.

[0017] Preferably, the boron-containing inorganic compound in step S1 is one or more of sodium borate, potassium tetraborate, lithium tetraborate, and ammonium borate.

[0018] Preferably, the mass ratio of the boron-containing inorganic compound, water and inorganic alkaline compound in step S1 is 1-4:28-42:1-4.

[0019] Preferably, the inorganic alkaline compound in step S1 is one or more of inorganic oxides such as nano-alumina, aluminum hydroxide, magnesium hydroxide, boehmite, and silicon dioxide, and the concentration of the borate ion aqueous solution in step S1 is 1%-10%.

[0020] Preferably, the usage ratio of 4-vinylbenzeneboronic acid, ethylene glycol divinyl ether, 3-chloro-2-hydroxypropyltrimethylammonium chloride, azobisisobutyronitrile, tetrahydrofuran and water in step S2 is 20-40g:30-50g:220-240mg:18-20mg:95-100mL:2-3mL.

[0021] Preferably, the mass ratio of the inorganic boric acid aqueous solution to the organic boric acid aqueous solution in step S3 is 30-50:10-15.

[0022] A method for preparing a highly heat-resistant and highly liquid-absorbent ceramic diaphragm comprises the following steps:

[0023] S11. The dispersant and deionized water were mixed evenly, ceramic particles were added, stirred evenly and ground for 10-50min to obtain a dispersion 1;

[0024] S12. Add a binder to the dispersion 1, stir for 30-60 min, then add a hydroxyl-containing polymer, stir for 30-60 min to obtain a mixed solution 2;

[0025] S13. Add the additive to the mixture 2, stir for 30-60 min, pass through a magnetic filtration device, stir for 5-20 min, and filter with a 250 mesh filter to obtain a slurry;

[0026] S14. The slurry is coated on the substrate by micro-gravure, dried, and then immersed in a boron-containing cross-linking agent for 10-20 minutes to cure to obtain a ceramic diaphragm.

[0027] The invention discloses an application of a highly heat-resistant and highly liquid-absorbent ceramic diaphragm, wherein the ceramic diaphragm can be applied to new secondary batteries such as lithium-ion batteries and sodium-ion batteries.

[0028] Beneficial effects of the present invention:

[0029] The present invention provides a highly heat-resistant and highly liquid-absorbent ceramic diaphragm and a preparation method and application thereof. A hydroxyl-containing polymer is introduced into the coating. Since the hydroxyl-containing polymer has good affinity for the electrolyte, the ceramic diaphragm has good liquid-absorption performance, thereby effectively improving the cycle performance of the battery cell.

[0030] The present invention provides a highly heat-resistant and highly liquid-absorbent ceramic diaphragm and a preparation method and application thereof. A boron-containing crosslinking agent is introduced into a coating. Since borate ions in an inorganic boric acid aqueous solution can act as a crosslinking agent and undergo a crosslinking reaction with a hydroxyl-containing polymer, 4-vinylphenylboric acid and ethylene glycol divinyl ether in an organic boric acid solution copolymerize to form a copolymer, which can form a six-membered ring at high temperature and form a three-dimensional network structure inside the coating. Therefore, the skeleton strength of the ceramic diaphragm is improved, thereby significantly improving the temperature resistance of the ceramic diaphragm. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0032] Embodiment 1: A method for preparing a highly heat-resistant and highly liquid-absorbent ceramic diaphragm, comprising the following steps:

[0033] S1. Dissolve 1g of sodium borate in 28g of water, and then add 1g of nano-alumina to obtain an inorganic boric acid aqueous solution with a concentration of 1%;

[0034] S2. 20 g of 4-vinylbenzeneboronic acid, 30 g of ethylene glycol divinyl ether, 220 mg of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 18 mg of azobisisobutyronitrile, 95 mL of tetrahydrofuran and 2 mL of water were mixed and reacted at 75 ° C for 22 h to obtain an organic boronic acid solution;

[0035] S3. To 30 g of 1% aqueous solution of inorganic boric acid was added 10 g of organic boric acid solution to obtain a boron-containing crosslinking agent;

[0036] S4. 1 g of sodium polyacrylate and deionized water were mixed, 80 g of ceramic particles were added, stirred and ground for 10 min to obtain a dispersion 1;

[0037] S5. 3g of styrene-butadiene rubber was added to the dispersion 1, stirred for 30min, and then 4g of nano bamboo charcoal powder was added, stirred for 30min to obtain a mixed solution 2;

[0038] S6. 0.1 g of succinic acid was added to the mixture 2, stirred for 30 min, passed through a magnetic filtration device, stirred for 5 min, and filtered through a 250 mesh filter to obtain a slurry;

[0039] S7. The slurry is coated on one side of the polyethylene substrate by micro-gravure, dried, and then immersed in a boron-containing cross-linking agent for 10 minutes to solidify to obtain a ceramic diaphragm.

[0040] Embodiment 2: A method for preparing a highly heat-resistant and highly liquid-absorbent ceramic diaphragm, comprising the following steps:

[0041] S1. Dissolve 2 g of potassium tetraborate in water, and then add 2 g of aluminum hydroxide to obtain an inorganic boric acid aqueous solution with a concentration of 2.5%;

[0042] S2. 27 g of 4-vinylbenzeneboronic acid, 37 g of ethylene glycol divinyl ether, 227 mg of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 18.7 mg of azobisisobutyronitrile, 97.2 mL of tetrahydrofuran and 2.4 mL of water were mixed evenly and reacted at 78 ° C for 22.8 h to obtain an organic boronic acid solution;

[0043] S3. To 35 g of an aqueous solution of 2.5% inorganic boric acid was added 12 g of an aqueous solution of organic boric acid to obtain a boron-containing crosslinking agent;

[0044] S4. 1.25 g of ammonium polyacrylate and deionized water were mixed, 90 g of ceramic particles were added, stirred and ground for 20 min to obtain a dispersion 1;

[0045] S5. Add 3.5 g of polymethyl acrylate to the dispersion 1, stir for 37.5 min, then add 5 g of nanocellulose, stir for 37.5 min, to obtain a mixed solution 2;

[0046] S6. 0.2 g of fluoroalkyl methoxy ether alcohol was added to the mixture 2, stirred for 37.5 min, passed through a magnetic filtration device, stirred for 10 min, and filtered through a 250 mesh filter to obtain a slurry;

[0047] S7. The slurry is coated on one side of the polypropylene substrate by micro-gravure, dried, and then immersed in a boron-containing cross-linking agent for 12.5 minutes to be cured to obtain a ceramic diaphragm.

[0048] Embodiment 3: A method for preparing a highly heat-resistant and highly liquid-absorbent ceramic diaphragm, comprising the following steps:

[0049] S1. Dissolve 3 g of lithium tetraborate in water, and then add 3 g of magnesium hydroxide to obtain an 8% aqueous solution of inorganic boric acid;

[0050] S2. 34 g of 4-vinylbenzeneboronic acid, 44 g of ethylene glycol divinyl ether, 234 mg of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 19.4 mg of azobisisobutyronitrile, 98.5 mL of tetrahydrofuran and 2.8 mL of water were mixed and reacted at 82 ° C for 23.6 h to obtain an organic boronic acid solution;

[0051] S3. To 45 g of an 8% aqueous solution of inorganic boric acid was added 14 g of an organic boric acid solution to obtain a boron-containing crosslinking agent;

[0052] S4. 1.8 g of sodium carboxylate and deionized water were mixed, 110 g of ceramic particles were added, stirred and ground for 40 min to obtain a dispersion 1;

[0053] S5. 4.5 g of polybutyl acrylate was added to the dispersion 1, stirred for 50 min, and then 7 g of polyvinyl alcohol was added and stirred for 50 min to obtain a mixed solution 2;

[0054] S6. 0.4 g of sodium polyacrylate was added to the mixture 2, stirred for 50 min, and then passed through a magnetic filtration device, stirred for 16 min, and filtered through a 250 mesh filter to obtain a slurry;

[0055] S7. The slurry is coated on one side of the polymethylpentene substrate by micro-gravure coating, dried, and then immersed in a boron-containing cross-linking agent for 18 minutes to be cured to obtain a ceramic diaphragm.

[0056] Embodiment 4: A method for preparing a highly heat-resistant and highly liquid-absorbent ceramic diaphragm, comprising the following steps:

[0057] S1. Dissolve 4 g of lithium tetraborate in water, and then add 4 g of magnesium hydroxide to obtain an inorganic boric acid aqueous solution having a concentration of 10%;

[0058] S2. 40 g of 4-vinylbenzeneboronic acid, 50 g of ethylene glycol divinyl ether, 240 mg of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 20 mg of azobisisobutyronitrile, 100 mL of tetrahydrofuran and 3 mL of water were mixed and reacted at 85 ° C for 24 h to obtain an organic boronic acid solution;

[0059] S3. To 50 g of a 10% aqueous solution of inorganic boric acid was added 15 g of an organic boric acid solution to obtain a boron-containing crosslinking agent;

[0060] S4. 2g of sodium carboxylate and deionized water were mixed, 120g of ceramic particles were added, stirred and ground for 50min to obtain a dispersion 1;

[0061] S5. 5 g of polybutyl acrylate was added to the dispersion 1, stirred for 60 min, and then 8 g of polyvinyl alcohol was added and stirred for 60 min to obtain a mixed solution 2;

[0062] S6. 0.5 g of sodium polyacrylate was added to the mixture 2, stirred for 60 min, and then passed through a magnetic filtration device, stirred for 20 min, and filtered through a 250 mesh filter to obtain a slurry;

[0063] S7. The slurry is coated on one side of the polymethylpentene substrate by micro-gravure, dried, and then immersed in a boron-containing cross-linking agent for 20 minutes to be cured to obtain a ceramic diaphragm.

[0064] Comparative Example 1:

[0065] This comparative example uses a polyethylene substrate with a thickness of 12 μm as a comparison.

[0066] Comparative Example 2:

[0067] Compared with Example 1, this comparative example only replaces "ethylene glycol divinyl ether" with "4-vinylbenzene boronic acid", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a ceramic diaphragm is obtained.

[0068] Comparative Example 3:

[0069] Compared with Example 1, this comparative example only replaces "4-vinylbenzeneboric acid" with "ethylene glycol divinyl ether", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a ceramic diaphragm is obtained.

[0070] Comparative Example 4:

[0071] Compared with Example 1, this comparative example does not add "organic boric acid solution" during the preparation of the ceramic diaphragm, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a ceramic diaphragm is obtained.

[0072] Comparative Example 5:

[0073] Compared with Example 1, this comparative example does not add "inorganic boric acid aqueous solution" during the preparation of the ceramic diaphragm, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a ceramic diaphragm is obtained.

[0074] Performance Testing

[0075] Referring to GB / T6672-2001 "Mechanical measurement method for the determination of thickness of plastic films and sheets", the thickness of each group of samples in Examples 1-4 and Comparative Examples 1-5 was measured using a THI-1801 thickness gauge in μm;

[0076] Referring to GB / T135I9-2016 standard, the thermal shrinkage rate (%) of each group of samples in Examples 1-4 and Comparative Examples 1-5 placed in an environment of 150° C. for 1 hour was measured using a FST-3102 film thermal shrinkage performance tester;

[0077] Referring to ISO15105-1:2007 "Plastics-Film and Sheeting Part 1: Diferential pressure Methods" standard, the air permeability value s / 100ml of each group of samples in Examples 1-4 and Comparative Examples 1-5 was measured using a GTR-704R air permeability meter;

[0078] Referring to QB / T2303.11-2008 "Battery pulp layer paper Part 11: Determination of liquid absorption rate", the liquid absorption rate of each group of samples in Examples 1-4 and Comparative Examples 1-5 was measured by weighing method, and each group of samples to be tested was immersed in the electrolyte for 120 minutes to obtain the liquid absorption rate. The calculation formula of the liquid absorption rate is as follows:

[0079] ε(%)=[(M 1 -M 0 )] / M 0 ×100%

[0080] Where ε is the liquid absorption rate (%); M 0 is the dry film mass (g); M 1 is the mass of wet film (g);

[0081] Referring to GB / T30447-2013 standard, the contact angle of each group of samples in Examples 1-4 and Comparative Examples 1-5 to the electrolyte was measured using a JC2000D1 contact angle tester;

[0082] Referring to GB / T36363-2018 standard, the tensile strength of each group of samples in Examples 1-4 and Comparative Examples 1-5 at 25°C and 80°C was measured using an AGS-J universal tensile testing machine. The results are shown in Table 1 below:

[0083] Table 1

[0084]

[0085]

[0086] Data Analysis:

[0087] As can be seen from Table 1, the ceramic diaphragm prepared in the present invention has a high liquid absorption rate, a low thermal shrinkage rate, and a high tensile strength at both high and low temperatures. By introducing a hydroxyl-containing polymer and a boron-containing crosslinking agent into the coating, the hydroxyl-containing polymer has good affinity for the electrolyte, so that the ceramic diaphragm has good liquid absorption performance, thereby effectively improving the cycle performance of the battery core, and the borate ions in the inorganic boric acid aqueous solution can be used as a crosslinking agent to react with the hydroxyl-containing polymer, and the 4-vinylphenylboric acid and ethylene glycol divinyl ether in the organic boric acid solution will form a copolymer of alternating phenylboric acid and ether bonds after copolymerization, wherein the phenylboric acid part can form a six-membered ring at high temperature, and the presence of a flexible ether bond can allow phenylboric acid to rotate, so that the degree to which phenylboric acid participates in the formation of the six-membered ring is more thorough, because a three-dimensional network structure can be formed inside the coating, the skeleton strength of the ceramic diaphragm is improved, and then the temperature resistance of the ceramic diaphragm is significantly improved, so that the prepared ceramic diaphragm has high mechanical properties in a wider temperature range.

[0088] In Comparative Example 2, ethylene glycol divinyl ether is used to replace 4-vinyl phenyl boronic acid. There is only a homopolymer of 4-vinyl phenyl boronic acid in the system. Similarly, no organic boric acid solution is added in Comparative Example 4. At this time, hydrogen bonds are formed between the borate ions in the inorganic boric acid aqueous solution and the hydroxyl-containing polymer. However, when the temperature rises, the hydrogen bonds are unstable, which causes the performance of the ceramic diaphragm to decline. In Comparative Example 3, 4-vinyl phenyl boronic acid is used to replace ethylene glycol divinyl ether. The hydrogen bonds between the borate ions and the hydroxyl-containing polymer will be unstable when the temperature rises, but the homopolymer of 4-vinyl phenyl boronic acid can form a six-membered ring inside the system, and the coating A three-dimensional network structure is formed inside, which increases the heat resistance of the ceramic diaphragm and provides space for the electrolyte, which improves the liquid retention of the battery diaphragm, thereby further increasing the cycle performance of the battery. In Comparative Example 5, no inorganic boric acid aqueous solution was added to the system. Therefore, at low temperatures, the system exists in the form of a hydroxyl-containing polymer and a copolymer of 4-vinylbenzeneboronic acid and ethylene glycol divinyl ether. When the temperature rises, a six-membered ring is formed between the copolymer of 4-vinylbenzeneboronic acid and ethylene glycol divinyl ether, forming a three-dimensional network structure inside the system. Therefore, the mechanical properties of the ceramic diaphragm are better after heating.

[0089] It should be understood by those of ordinary skill in the art that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples; within the context of the present invention, the technical features in the above embodiments or in different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A highly heat-resistant and highly liquid-absorbent ceramic diaphragm, characterized in that: The invention comprises a coating and a substrate, wherein the coating is prepared from the following raw materials in parts by weight: 80-120 parts of ceramic particles, 4-8 parts of hydroxyl-containing polymers, 3-5 parts of a binder, 30-50 parts of a boron-containing crosslinking agent, 0.1-0.5 parts of an auxiliary agent, and 1-2 parts of a dispersant; The substrate is composed of any one of polyethylene, polypropylene and polymethylpentene; The preparation method of the boron-containing cross-linking agent is as follows: S1. dissolving the boron-containing inorganic compound in water, and then adding an inorganic alkaline compound to obtain an inorganic boric acid aqueous solution; S2. 4-vinylbenzeneboronic acid, ethylene glycol divinyl ether, 3-chloro-2-hydroxypropyltrimethylammonium chloride, azobisisobutyronitrile, tetrahydrofuran and water are mixed evenly, and reacted at 75-85° C. for 22-24 hours to obtain an organic boronic acid solution; S3. Evenly mix the inorganic boric acid aqueous solution and the organic boric acid solution to obtain a boron-containing crosslinking agent.

2. A highly heat-resistant and highly liquid-absorbent ceramic diaphragm according to claim 1, characterized in that: The hydroxyl-containing polymer is one or more of nano bamboo charcoal powder, nano cellulose, polyvinyl alcohol, polyethylene glycol, and the binder is one or more of styrene-butadiene rubber, polymethyl acrylate, polybutyl acrylate, polyvinyl alcohol, polyvinylidene fluoride, etc.

3. A highly heat-resistant and highly liquid-absorbent ceramic diaphragm according to claim 1, characterized in that: The auxiliary agent is one or more of succinic acid, fluoroalkyl methoxy ether alcohol, sodium polyacrylate, acetylene glycol vinyl ether, fatty acid polyoxyethylene ether, and polyether modified siloxane; the dispersant is one or more of sodium polyacrylate, ammonium polyacrylate, carboxylates, and sulfonates.

4. A highly heat-resistant and highly liquid-absorbent ceramic diaphragm according to claim 1, characterized in that: The boron-containing inorganic compound in step S1 is one or more of sodium borate, potassium tetraborate, lithium tetraborate, and ammonium borate.

5. The high heat-resistant and high liquid-absorbing ceramic diaphragm according to claim 1, characterized in that: The mass ratio of the boron-containing inorganic compound, water and inorganic alkaline compound in step S1 is 1-4:28-42:1-4.

6. A highly heat-resistant and highly liquid-absorbent ceramic diaphragm according to claim 1, characterized in that: The inorganic alkaline compound in step S1 is one or more of inorganic oxides such as nano-alumina, aluminum hydroxide, magnesium hydroxide, boehmite, and silicon dioxide. The concentration of the borate ion aqueous solution in step S1 is 1%-10%.

7. The high heat-resistant and high liquid-absorbing ceramic diaphragm according to claim 1, characterized in that: The usage ratio of 4-vinylbenzeneboronic acid, ethylene glycol divinyl ether, 3-chloro-2-hydroxypropyltrimethylammonium chloride, azobisisobutyronitrile, tetrahydrofuran and water in step S2 is 20-40 g: 30-50 g: 220-240 mg: 18-20 mg: 95-100 mL: 2-3 mL.

8. The high heat-resistant and high liquid-absorption ceramic diaphragm according to claim 1, characterized in that: The mass ratio of the inorganic boric acid aqueous solution to the organic boric acid aqueous solution in step S3 is 30-50:10-15.

9. A method for preparing a highly heat-resistant and highly liquid-absorbent ceramic diaphragm according to any one of claims 1 to 8, characterized in that: The following steps are involved: S11. The dispersant and deionized water were mixed evenly, ceramic particles were added, stirred evenly and ground for 10-50min to obtain a dispersion 1; S12. Add a binder to the dispersion 1, stir for 30-60 min, then add a hydroxyl-containing polymer, stir for 30-60 min to obtain a mixed solution 2; S13. Add the additive to the mixture 2, stir for 30-60 min, pass through a magnetic filtration device, stir for 5-20 min, and filter with a 250 mesh filter to obtain a slurry; S14. The slurry is coated on the substrate by micro-gravure, dried, and then immersed in a boron-containing cross-linking agent for 10-20 minutes to cure to obtain a ceramic diaphragm.

10. An application of the high heat-resistant and high liquid-absorption ceramic diaphragm according to any one of claims 1 to 8, characterized in that: The ceramic diaphragm can be applied to lithium ion batteries and sodium ion batteries.

Citation Information

Patent Citations

  • A ceramic-coated diaphragm, its preparation method, and its application.

    CN108305972B

  • Battery diaphragm coating liquid and preparation method thereof, battery diaphragm and battery

    CN113964450A

  • Lithium battery coating diaphragm with low water content and preparation method of lithium battery coating diaphragm

    CN109742293A

  • Gel electrolyte electrode, diaphragm, lithium ion battery and preparation methods of gel electrolyte electrode, diaphragm and lithium ion battery

    CN116979152A

  • Gel electrolyte electrode, diaphragm, lithium ion battery and preparation methods of gel electrolyte electrode, diaphragm and lithium ion battery

    CN118841633A